The determinants of Malaysian Ringgit - Musa, Muhammad Nazmy Rezzaimy; Mohd Johar, Siti Zaleha (2016)
This paper investigate the determinants of Malaysian Ringgit (MYR) using import, export, world oil price and financing rate as independent variables for 30 years from the period of 1986 to 2015. The relationship is examined by regression analysis using time series data that were collected from various sources. The purpose of this study is to investigate the relationship between selected variables by testing through Multiple Linear Regression whether it have positive or negative relationship towards one another. The model were tested by using E-views software. Through Multiple Linear Regression, study shows that import, export and world oil price has no significant effect towards Malaysian Ringgit. Meanwhile, financing rate has a significant effect towards Malaysian Ringgit.